Influence of Polymer Coating on Nursery Management in Chillies - P. GEETHARANI; A.S. PONNUSWAMY; P. SRIMATHI (Seed Research, 2026)
Studies were made to elucidate the influence of hydrophilic polymer coating with and without pesticides and DAP on seed and seedling quality characteristics of chilli cv. K2. The results showed that slurry coating of seed with polykote (3g kg¹ of seed) along with carbendazim (2g kg of seed) and halogen mixture (3g kg seed) enhanced aced the germination and vigour index values by 24 per cent, whereas, the pathogen infection was lessened by 1 per cent compared to uncoated seeds. This treatment also enhanced the field emergence by 29 per cent in the nursery sowing.